Getting to “Yes”: Overcoming Client Reluctance to Engage in Chair Work - Muntigl, Peter; Horvath, Adam O.; Chubak, Lynda; Angus, Lynne (Frontiers in Psychology, 2020)
Goals Securing clients’ active and enthusiastic collaboration to participate in activities therapists would like to implement in therapy (e.g., free association, in-vivo exposure, or the engagement in chair work) is a core mission in therapy. However, from the clients’ perspective, these tasks frequently represent novel challenges that can trigger anxiety and reluctance. Thus, a key element in therapy is the negotiation between therapist and client to move beyond such reluctance to potentially effective therapy activities and, at the same time, maintain positive relational affiliation between therapist and client. In this research we examined 1) a collection of therapist proposal/client response sequences that were geared toward recruiting participation in chair work and 2) sequences containing hesitation or instances where decisions to engage in chair work were deferred and related relational disaffiliation. Our goal was to identify the conversational resources (both verbal and non-verbal) that worked to reject a proposed activity (or convey impending rejection) and examine the interactional practices directed at resolving client reluctance. Method We used the conceptual and methodological resources of Conversation Analysis to examine a corpus of proposal/response sequences that targeted chair work entry in Emotion-focused Therapy. Results The resulting data set included some smooth and successful engagements and others more challenging, involving clients delaying or resisting engagement with chair work. Clients were found to defer or refuse engagement through a range of resources such as withholding a response (silence), questioning the authenticity of the task, or directly refusing. We identified specific therapist practices that facilitated engagement in ‘refusal-implicative’ contexts such as proffering “or” alternatives, offering extended rationales for the activity (accounting), and elaborating on the proposals. We observed that the therapists’ deontic stance (mitigated and reduced claims to authority) and moderated epistemic positioning (deference to the client’s primacy of knowledge and information) played an important role in facilitating engagement. Conclusions Our research highlights the kinds of interactional sequences in which clients and therapists are able to achieve alignment in mutually working towards chair work entry. Based on these observations, we offer some practical advice to therapists in formulating proposals to engage clients during in-therapy work.